Utilizing geographical information systems (gis) & satellite remote sensing analysis for integrated planning: A case study of paphos district area - Unesco world heritage town (Paphos, Cyprus) - Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos (My University, 2007)
Preservation of the World Heritage Site and historic district in Paphos will ultimately depend upon understanding the interrelationship among a variety of cultural and natural parameters. Indeed, for tracing such a situation, a landscape analysis utilizing remote sensing and GIS technology is being conducted at the Paphos District area in Cyprus in the service of planning for a revitalized town that will preserve not only historic sites, but traditional cultural forms as well. A successful plan and implementation will provide an opportunity to local decision makers to provide a synoptic and detailed planning of the town. Indeed, high resolution (QUICKBIRD, IKONOS) and medium resolution (Landsat ETM+, SPOT) satellite images have been used in conjunction with topographical and other auxiliary data in this study. The GIS will serve as an "intelligent" database, which will provide a compact space where all sorts of data relevant to Paphos cultural sites can be stored in digital format, including images, maps, documents, photographs, and even audio recordings. More importantly, data will be arranged so that it can be incorporated into displays like maps, charts, and tables, and can be queried in the service of sophisticated analytical procedures. Future analyses can be the basis for future planning, design, and site management decisions. This study shows only the methodology proposed by the authors in this project and the first results obtained from its application.
Keywords: Database; Decision making; GIS; Maps; Planning; Remote Sensing